2014
DOI: 10.1158/1078-0432.ccr-13-0171
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Circadian Clock Gene Bmal1 Increases Sensitivity to Oxaliplatin in Colorectal Cancer

Abstract: Purpose: The circadian clock gene Bmal1 is involved in cancer cell proliferation and DNA damage sensitivity. The aim of this study was to explore the effect of Bmal1 on oxaliplatin sensitivity and to determine its clinical significance in colorectal cancer.Experimental Design: Three colorectal cancer cell lines, HCT116, THC8307 and HT29, were used. The Bmal1-mediated control of colorectal cancer cell proliferation was tested in vitro and in vivo. MTT and colony formation assays were performed to determine the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
113
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 48 publications
(51 reference statements)
18
113
0
Order By: Relevance
“…Moreover, irinotecan cytotoxicity appeared to be positively correlated to the expression level of clock gene BMAL1, both in clock-proficient and in clock-deficient cells. In contrast, the cytotoxicity of oxaliplatin, another effective anticancer drug against colorectal cancer, reportedly displayed a negative correlation with BMAL1 expression level (33). Taken together, the findings suggest that BMAL1 tumor expression could help select the most effective drug for a given patient.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, irinotecan cytotoxicity appeared to be positively correlated to the expression level of clock gene BMAL1, both in clock-proficient and in clock-deficient cells. In contrast, the cytotoxicity of oxaliplatin, another effective anticancer drug against colorectal cancer, reportedly displayed a negative correlation with BMAL1 expression level (33). Taken together, the findings suggest that BMAL1 tumor expression could help select the most effective drug for a given patient.…”
Section: Discussionmentioning
confidence: 92%
“…These findings provide a mechanistic foundation for the delayed onset of tumorigenesis in clock-disrupted p53 mutant mice, giving a note of optimism in treating cancers associated with p53 mutation [37]. In humans, the expression level of TIM was higher in the tumor tissue of colorectal cancer patients, while the overexpression of the circadian clock gene BMAL1 increases sensitivity to oxaliplatin in patients with colorectal cancer [38,39]. Mazzoccoli evaluated chronodisruption in lung cancer; actually, he found that in patients with lung cancer, GH, IGF1, TRH, TSH, FT4, cortisol and IL2 values did not show rhythmic variation [40].…”
Section: Clock-work Dysfunction and Cancermentioning
confidence: 83%
“…High BMAL1 levels in the primary tumour in pa ents with colorectal cancer were associated with longer overall survival (>1.5 mes) than the overall survival rates in pa ents with tumours with low BMAL1 levels [36]. Similarly, the progression-free survival in pa ents with colorectal tumours expressing BMAL1 at high levels was es mated to be almost twice as long as the progression-free survival in pa ents with tumours expressing BMAL1 at low levels [36].…”
Section: Genotype-phenotype Correlations For Mutations and Polymorphimentioning
confidence: 88%
“…Timing of an cancer therapy around the circadian cycle may increase its efficacy and minimise the associated adverse effects [36] (for more informa on also see below).…”
mentioning
confidence: 99%